Prediction and improved characterization of coiled-coil protein origami nanostructures by comparative modeling - Mandal, Ratnakshi (Kansas State University, 2022)
Coiled-coil protein origami (CCPO) is a method that connects and folds coiled-coil protein modules into well-defined nanostructures, which offer a great promise in the fields of nanotechnology and biomaterials. In the determination of atomistic details of a CCPO nanostructure, small-angle X-ray scattering (SAXS) has been used in combination with comparative protein structure modeling. The modeling utilizes a critical step of molecular dynamics (MD) optimization with simulated annealing for structure refinement, but the details of the optimization and reliable evaluation for CCPO models are not available. In this report, the effect of MD optimization on the accuracy of comparative modeling was studied by the fitting of SAXS data. Under extended MD optimization, structural models of nearly complete matches to SAXS data were built. In addition, a method of predicting the radius of gyration of comparative structure models was developed, which enabled a significantly improved evaluation of the comparative models of CCPO. It will provide great potential as a method for computational screening of CCPO designs.
Keywords: Coiled coil proteins; Small angle x-ray scattering; Protein origami; Comparative modeling